Constitutively active Foxo3 in oocytes preserves ovarian reserve in mice - Pelosi, Emanuele; Omari, Shakib; Michel, Marc; Ding, Jun; Amano, Tomokazu; Forabosco, Antonino; Schlessinger, David; Ottolenghi, Chris (Nature communications, 2013)
During female reproductive life, ovarian follicle reserve is reduced by maturation and atresia until menopause ensues. Foxo3 is required to maintain the ovarian reserve in mice. Here we show that overexpression of constitutively active FOXO3 can increase ovarian reproductive capacity in mice. We find increased follicle numbers and decreased gonadotropin levels in aging FOXO3 -transgenic mice compared with wild-type littermates, suggesting maintenance of a greater ovarian reserve. Based on cumulative progeny in aging animals, we find 31–49% increased fertility in transgenic females. The gene expression profile of Foxo3−/− knockout ovaries appears older than that of wild-type littermates, and the transgene induces a younger-looking profile, restoring much of the wild-type transcriptome. This is the first gain-of-function model of augmented reproductive reserve in mice, thus emphasizing the role of Foxo3 as a guardian of the ovarian follicle pool in mammals and a potential determinant of the onset of menopause. The number of primordial follicles, which constitute the ovarian reserve, decreases with age. By overexpressing a constitutively active version of the transcription factor FOXO3, the authors increase the ovarian reserve and fertility in aging female mice.